2020
DOI: 10.1002/jlb.2a0720-432r
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric targeting of the FFA2 receptor (GPR43) restores responsiveness of desensitized human neutrophils

Abstract: The G protein-coupled free fatty acid receptor 2 (FFA2R) is highly expressed on neutrophils and was previously described to regulate neutrophil activation. Allosteric targeting of G proteincoupled receptors (GPCRs) is increasingly explored to create distinct pharmacology compared to endogenous, orthosteric ligands. The consequence of allosteric versus orthosteric FFA2R activation for neutrophil response, however, is currently largely elusive. Here, different FFA2R desensitization profiles in human neutrophils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
(110 reference statements)
1
8
0
Order By: Relevance
“…But irrespective of the precise mechanism that transfers FFA2R to a biased desensitized state, the selectively desensitized receptor can still be activated. These results are in agreement with the results presented in a study using another slightly different allosteric FFA2R ligand (4-CMTB) showing that that desensitized FFA2Rs may be reactivated by a mechanism designed to safeguard FFA2R function and by that preserve the neutrophil responsiveness to othosteric FFA2R agonists [38]. The precise signals generated when AZ1729 is used to activate the cells can only be speculated on, but it is clear that an oxidase activating signal was generated also when the "biased desensitized" FFAR2s were activated by this modulating ligand.…”
Section: +supporting
confidence: 92%
See 1 more Smart Citation
“…But irrespective of the precise mechanism that transfers FFA2R to a biased desensitized state, the selectively desensitized receptor can still be activated. These results are in agreement with the results presented in a study using another slightly different allosteric FFA2R ligand (4-CMTB) showing that that desensitized FFA2Rs may be reactivated by a mechanism designed to safeguard FFA2R function and by that preserve the neutrophil responsiveness to othosteric FFA2R agonists [38]. The precise signals generated when AZ1729 is used to activate the cells can only be speculated on, but it is clear that an oxidase activating signal was generated also when the "biased desensitized" FFAR2s were activated by this modulating ligand.…”
Section: +supporting
confidence: 92%
“…Such a response was induced when the allosteric FFA2R modulator AZ1729 was used as the co-activating ligand. The mechanisms that determine nonresponsiveness/desensitization of neutrophil GPCRs such as the FFA2Rs are very complex and may be dependent on changes at the receptor level as well as at the down-stream signaling level [38][39][40]. But irrespective of the precise mechanism that transfers FFA2R to a biased desensitized state, the selectively desensitized receptor can still be activated.…”
Section: +mentioning
confidence: 99%
“…Previous studies have provided pharmacologic and genetic evidence about the chemotactic potential of GPR43 stimulation in neutrophils. In this regard, it has been shown that mouse and human neutrophils migrate towards SCFA in transwell assays [53][54][55][56]. Here we described how GPR43-signalling induced the selective chemotaxis of IEL TCRαβ + T-cells into the colonic epithelium.…”
Section: Discussionmentioning
confidence: 63%
“…Indeed, several reports clearly demonstrated that FFAR2 promotes chemotaxis in mouse and human neutrophils. Beyond migratory response, FFAR2 also accounts for other central neutrophils traits, such as adhesion, rolling, transmigration, phagocytosis, and killing mechanisms, such as granule formation and trafficking or oxidative burst [20,[130][131][132][133][134][135]. In addition to an offensive first line host defense, neutrophils also regulate and end overt inflammatory host responses.…”
Section: Inflammation and Immune Functionmentioning
confidence: 99%
“…Moreover, Frei et al revealed distinct signaling compositions of Gαi/o-and Gαq/11-dependent as well as Gi/q-independent pathways between orthosteric and allosteric FFAR2 activations in neutrophils with propionate and 4-CMTB, respectively. Furthermore, it was shown that allosteric targeting of FFAR2 can resensitize the receptor and render previously silenced neutrophils selectively responsive toward orthosteric FFAR2 activation [133]. Although the molecular mechanisms underlying the allosteric modulation of FFAR2 still need to be fully elucidated, the phenomenon of allosteric rescue of a desensitized FFA2 receptor could potentially open novel avenues of drug discovery approaches.…”
Section: Inflammation and Immune Functionmentioning
confidence: 99%